DIDIKAN BUDAYA BERBAGI DI RAMADHAN 1443 H KE-20 HIMFAH – UPMI BAGIKAN TA’JIL DI PANTI ASUHAN MAMIYAI JALAN BROMO KOTA MEDAN - Dewi Robiyanti (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
This study aims to discuss the phenomenon of sharing takjil during Ramadan in Indonesia, the study of ma'anil hadith. This research is a qualitative type that applies literature study by applying the hadith maudhu'i method with a cultural perspective with a phenomenological approach. The results and discussion of this research covers the phenomenon of sharing takjil during Ramadan in Indonesia, ma'anil hadith sharing takjil during Ramadan, as well as the virtues and benefits of sharing takjil. This research concludes that the phenomenon of sharing takjil during Ramadan by people in Indonesia has a positive impact on people who accept takjil and has many virtues and benefits for takjil givers both in terms of hablumminannas (relations with fellow humans) and with habumminallah (relationship between creatures and the creator). This research recommends that this simple research be perfected and it is suggested to all Muslims to continue to preserve the phenomenon of sharing takjil because there are many benefits and virtues.